KRITIK USUL FIKIH ATAS QIYĀS DAN ḤUKM WAḌ‘Ī DALAM PERGUB NTB NOMOR 15 TAHUN 2016 - Juandi, Wawan; Khotib, A. Muhyiddin; Assakoti, Sari; Nahe’i, Nahe’i (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2025)
Professional zakat is a contemporary issue in Islamic law that has emerged alongside changes in the modern economic structure, particularly the dominance of the service sector and bureaucracy. In Indonesia, professional zakat is not only developed through fiqh discourse. Still, it is also institutionalized through public policies, such as the Governor of West Nusa Tenggara Number 15 of 2016 concerning the management of professional zakat for the State Civil Apparatus (ASN). This article aims to analyze these policies from the perspective of fiqh and fiqh proposals, with an emphasis on the validity of the Qiyās method and the application of the structure of ḥukm waḍ'ī zakat. This study employs a juridical-normative approach, analyzing classical and contemporary fiqh literature. The results of the survey show that professional zakat is a matter of ijtihadiyyah, disputed among scholars, and its determination as an administrative obligation through regional regulations may raise methodological concerns, particularly regarding qiyās Ma'a Al-Fāriq and the neglect of zakat conditions and barriers. Therefore, it is necessary to reformulate the professional zakat policy to align more closely with the principles of Islamic law.